STRATEGI PELESTARIAN TRADISI NGELEMANG SEBAGAI WARISAN KULINER BUDAYA PADA GENERASI MUDA DI LAMPUNG BARAT - Egi Gusti Al Fajri; Rizky Agung Abadi; Rahmat Prayogi (STKIP Pesisir Selatan, 2025)
Indonesia is a nation with a rich diversity of cultures, due to its hundreds of millions of inhabitants from various ethnic groups spread from Sabang to Merauke. This is in line with Maulida's opinion that Indonesian culture is a combination of various local cultures found in every region of Indonesia. This culture continues to evolve over time, influenced by the community's desire for change and adaptation in cultural aspects.Culture is an important element that binds individuals in society, encompassing various systems such as beliefs and traditions. Indonesia, with its cultural diversity, has many traditions that have been passed down from generation to generation. One example is the Ngelemang tradition in Lampung, which is the process of cooking lemang, a traditional food made from sticky rice. In this study, qualitative and ethnographic methods were used to understand the essence and preservation of this tradition. Ngelemang is not just a cooking activity, but also a means of strengthening social interaction and communal identity. Preservation strategies involve the active role of the younger generation, who are expected to not only be successors but also promoters through digital media, so that this tradition remains alive and relevant in everyday life.